Randomized Phase II Trial of Parsatuzumab (Anti‐EGFL7) or Placebo in Combination with Carboplatin, Paclitaxel, and Bevacizumab for First‐Line Nonsquamous Non‐Small Cell Lung Cancer - von Pawel, Joachim; Spigel, David R.; Ervin, Thomas; Losonczy, György; Barlesi, Fabrice; Juhász, Erzsébet; Anderson, Maria; McCall, Bruce; Wakshull, Eric; Hegde, Priti; Ye, Weilan; Chen, Daniel; et al. (The oncologist (Dayton, Ohio), 2018)
Lessons Learned The lack of efficacy associated with anti‐EGFL7 combined with standard bevacizumab and chemotherapy in this phase II trial in non‐small cell lung carcinoma is consistent with the lack of benefit observed in colorectal carcinoma, highlighting the challenge of enhancing the efficacy of VEGF inhibition in unselected populations. Future efforts with agents like anti‐EGFL7 should be guided by advances in pharmacodynamic and predictive biomarker development for antiangiogenic agents. Background Epidermal growth factor‐like domain 7 (EGFL7) is an extracellular matrix‐associated protein that is upregulated during angiogenesis and supports endothelial cell survival. This phase II trial evaluated the efficacy of the anti‐EGFL7 antibody, parsatuzumab, in combination with bevacizumab plus platinum‐based therapy for advanced or recurrent nonsquamous non‐small cell lung cancer (NS‐NSCLC). Methods Patients (n = 104) were randomized to either placebo or parsatuzumab (600 mg) in combination with bevacizumab (15 mg/kg) and carboplatin/paclitaxel, administered on day 1 of each 21‐day cycle. Carboplatin and paclitaxel were administered for up to six cycles. Bevacizumab and parsatuzumab/placebo were administered for a maximum of 24 months. Results The progression‐free survival (PFS) hazard ratio (HR) was 1.7 (95% confidence interval [CI], 1.0–2.8; p = .047). The median PFS was 6.7 months for the parsatuzumab arm versus 8.1 months for the placebo arm. The hazard ratio for overall survival (OS) was 1.1 (95% CI, 0.5–2.2; p = .847). The objective response rate (ORR) was 29% in the parsatuzumab arm and 56% in the placebo arm. Overall safety and tolerability were consistent with the established toxicity profile of bevacizumab. Conclusion There was no evidence of efficacy for the addition of parsatuzumab to the combination of bevacizumab and chemotherapy for first‐line NS‐NSCLC. 经验总结 在此非小细胞肺癌II期试验中, EGFL7抗体联合贝伐单抗和化疗标准治疗缺乏疗效与在结直肠癌患者中观察到的缺乏获益的情况一致, 突出显示了在非选定人群中增强VEGF抑制效力的挑战。 今后有关EGFL7抗体等药物的工作应以抗血管生成药物的药效学和预测性生物标志物开发的进展为指导。 摘要 背景.表皮生长因子样结构域7（EGFL7）是一种细胞外基质相关蛋白, 在血管生成过程中得以上调, 可为内皮细胞存活提供支持。该II期临床试验评价了EGFL7抗体Parsatuzumab联合贝伐单抗加含铂方案治疗晚期或复发性非鳞状细胞非小细胞肺癌（NS‐NSCLC）的疗效。 方法.患者（n=104）被随机分入安慰剂组或Parsatuzumab（600 mg）联合贝伐单抗（15 mg/kg）和卡铂/紫杉醇组, 在各周期的第1天接受给药, 每一周期21天。卡铂和紫杉醇最多给药六周期。贝伐单抗和Parsatuzumab/安慰剂的最长给药时间为24个月。 结果.无进展生存期（PFS）风险比（HR）为1.7[95%置信区间（CI）, 1.0–2.8；p=0.047]。Parsatuzumab组与安慰剂组的中位PFS分别为6.7个月与8.1个月。总生存期（OS）风险比为1.1（95% CI, 0.5–2.2；p=0.847）。Parsatuzumab组和安慰剂组的客观缓解率（ORR）分别为29%和56%。总体安全性和耐受性与贝伐单抗的既定毒性特征一致。 结论.没有证据支持Parsatuzumab联合贝伐单抗和化疗一线疗法治疗NS‐NSCLC的疗效。